Metallographical and Thermodynamic Investigation of the Microstructures at 1200°C of TaC–Containing Co–Based Alloys - Patrice Berthod (Indonesian Journal of Innovation and Applied Sciences (IJIAS), 2022)
Among the wide variety of current metallic structural materials able to work at elevated temperatures in severe chemical and mechanical conditions, some superalloys based on cobalt play a particular role: the ones rich in chromium for resisting hot corrosion by gases and melts and strengthened by tantalum carbides. They are able to demonstrate good behavior in contact of molten salts or glasses and simultaneously under mechanical stresses. Their refractoriness as well as the characteristics of their TaC population are key points for their sustainability at high temperature in working conditions. The present study aims to anticipate the long time microstructure behavior at high temperature by testing three similar cast Co–based superalloys strengthened by TaC carbides but different from each other in the field of the chemical compositions of their matrix. Thermodynamic calculations and long time exposure at 1200°C were carried out to predict their microstructure evolution at this very high temperature, with special focus of the influence on TaC carbides of the chemical compositions of the alloys, notably of their matrix.